1997
DOI: 10.1172/jci119434
|View full text |Cite
|
Sign up to set email alerts
|

A decline in myometrial nitric oxide synthase expression is associated with labor and delivery.

Abstract: The mechanisms that maintain relative uterine quiescence during pregnancy remain largely unknown. A possible role for nitric oxide has recently emerged, however, the expression of nitric oxide synthase within human myometrium at midgestation, a time when the uterus is normally quiescent, has not been investigated. The purpose of this study was to identify cell types in human myometrium that contain inducible nitric oxide synthase (iNOS), and to examine changes in its expression during pregnancy and labor. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 38 publications
7
59
2
Order By: Relevance
“…However, we and others have shown that in mice, humans, and rats, NOS-2 is appropriately positioned in both spatial and temporal terms to have a major influence on pregnancy (11,20,21). Biosynthesis of NO is clearly critical; when NOS inhibitors are administered to pregnant rats, the result is severe maternal hypertension and fetal growth restriction, symptoms resembling pre-eclampsia in humans (22).…”
Section: Discussionmentioning
confidence: 92%
“…However, we and others have shown that in mice, humans, and rats, NOS-2 is appropriately positioned in both spatial and temporal terms to have a major influence on pregnancy (11,20,21). Biosynthesis of NO is clearly critical; when NOS inhibitors are administered to pregnant rats, the result is severe maternal hypertension and fetal growth restriction, symptoms resembling pre-eclampsia in humans (22).…”
Section: Discussionmentioning
confidence: 92%
“…NO have many important biological functions; the best known is the regulation of vascular tone [29]. The ability of exogenous NO to promote uterine relaxation is well documented.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of exogenous NO to promote uterine relaxation is well documented. NO donors have been shown to cause uterine relaxation, and to inhibit contractions in vivo in humans [29]. NO is considered to be an important local mediator that suppresses uterine contractility in rats and rabbits during pregnancy until term [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggest that there may be an interaction between NO and PG pathways in regulating the NOS and COX expression and this interaction may play a critical role in the control of cervical ripening and parturition (25,30). In addition, it has been shown that during pregnancy in both the rat and human, the endometrium expresses the enzyme iNOS, which produces nitric oxide, a smooth muscle relaxant (4,19).…”
Section: Introductionmentioning
confidence: 99%